"What choice do people have other than us?": The role of doctors' offices adjacent to private pharmacies in the Covid-19 pandemic - Ana Victoria Morán Pérez (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
With the arrival of coronavirus in Mexico, doctors' offices adjacent to private pharmacies (DAPPs) played a major role in the diagnosis, care, and prevention of Covid-19, providing treatment for 11.7% to 23% of people with Covid-19 symptoms according to national surveys. Therefore, this article seeks to identify the role of DAPPs as a private health system providing care for patients with Covid-19 symptoms in the city of Oaxaca, and to describe and analyze the factors that influenced their utilization. Using a qualitative methodology, twelve physicians were interviewed and 59 users responded to a questionnaire at doctors' offices adjacent to pharmacies in the municipality of Oaxaca de Juárez between September 2020 and August 2022. Secondary data were also collected. Among the findings, the function of these offices at the front line of care for Covid-19 and other health needs that emerged with the public health crisis is described, and the determining factors in care trajectories of users that sought care there are analyzed, such as the increase in perception of risk and mistrust towards public services or strategies implemented by the federal government.